PENGGUNAAN SARUNG TELUR MENTADAK DALAM PERUBATAN TRADISIONAL CINA MENURUT PERSPEKTIF FIQH KEPENGGUNAAN - Zubair Amir Nur Rashid; Nur Mardia Mazri (Malaysian Journal of Syariah and Law)
Consumer jurisprudence is a branch of the broad jurisprudential debate covering the utilization and use of all natural resources and their contents. Traditional Chinese Medicine as an alternative medicine uses natural resources as a source of medicine. The Mantidis Ootheca in Traditional Chinese Medicine is a substance that comes out through a special accessory gland on the abdomen of the mantis mother and then produces a foamy and hardened structure like polystyrene. It is believed to have various benefits including treating cloudy urine, kidney health, helping in treating Benign Prostatic Hyperplasia (BPH) and others. However, there is an issue involving the status of the Mantidis Ootheca from the perspective of Islamic law since the egg case is produced from the liquid that comes out through the mantis stomach. The focus of this paper was to clarify the Islamic legislation regarding the use of Mantidis Ootheca in the manufacture of pharmaceutical products from the standpoint of the consumer jurisprudence discussion. The researcher utilized a qualitative method by referring to books of fiqh and usul fiqh to find out the law of using Mantidis Ootheca in products and the liquid flowing from its stomach in medicine. This study emphasize on analyzing the application of rukhsah and istihalah in medicine in unraveling the problem of treatment using Mantidis Ootheca. Standards from halal authorities such as the Department Standards of Malaysia are also reviewed for pharmaceutical manufacturing rules including the requirement of safety assessment. Meanwhile, the researcher also consulted scientific studies to know the benefits, uses and side effects of Mantidis Ootheca in the medical field. According to the study's findings, the use Mantidis Ootheca in medicine is not halal since they are tainted with impurities (najāsah). The egg case that come from mantis are considered disgusting, according to scholars, and should not be eaten. Still, its use in pharmaceuticals needs to be evaluated from the perspective of medical jurisprudence by looking at its level of need in the field. Until now, its use is not reached to an emergency demand as there are still alternative treatments for the related diseases. Frequently it has been consumed as a health supplement rather than the primary component in medications. It also does not meet the safety standards determined by the jurists and according to the MS 2424: 2019 ruling based on current research showing that there is no comprehensive report on toxicity aspects and adverse side effects to users. The study of the pharmaceutical industry should continue to be pioneered by Muslims to ensure the use of halal ingredients in medicine.